Empowering Women through E-Learning: The Role of Waqf in Supporting Digital Education for Girls and Women in Northern Nigeria - Adamu Abubakar Muhammad; Mohammed Afolabi Idayat; Shafa’at Ahmad Aliyu; Mansir Hashimu; Bilkisu Mohammed Ovosi (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2024)
This study aims to investigate how women in Northern Nigeria might benefit from digital education through waqf, an Islamic endowment. To increase girls and women's access to education, the study focuses on determining how waqf institutions may aid in creating e-learning infrastructure, materials, and training initiatives. The study aims to eliminate social and economic hurdles that restrict women's access to education in the area, advance gender equality, and provide women with the skills necessary for socioeconomic development by utilizing waqf monies. The ultimate objective is to demonstrate how integrating digital education programs with Islamic charitable frameworks can establish long-term avenues for women's empowerment and promote wider community development in Northern Nigeria. Women's education greatly aids Social and economic progress, especially in areas with large gender gaps. Women's access to formal education has been hampered in Northern Nigeria by long-standing obstacles such as early marriage, poverty, and cultural conventions. However, the emergence of e-learning offers a special chance to close this gap by giving women and girls remote access to educational materials. This study uses a mixed-methods approach, this study investigates how Waqf supports e-learning for women in Northern Nigeria by integrating qualitative and quantitative research approaches. The results indicate that women's educational chances can be greatly improved by combining Waqf with online learning programs, enabling them to better their socioeconomic circumstances and make a positive impact on their communities. The study's conclusion emphasizes the necessity of deliberate actions to optimize Waqf's effectiveness in resolving gender-based educational disparities in Northern Nigeria.